2017
DOI: 10.5755/j01.ms.23.4.17469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Surface Modification Methods on Physical Properties of Hemp Fibers

Abstract: In this study, hemp fibers have been pre-treated with laccase enzyme in different concentrations (1 %, 2 % and 3 % w/v) for different durations using conventional, ultrasonic energy and microwave energy methods. Weight loss (%), tensile strength, elongation (%), whiteness (%), and surface topography (SEM) properties of pre-treated hemp fibers were investigated. After processing with laccase enzyme, the energy consumptions of these three methods were compared. Best results have been obtained in 20 minutes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The SEM micrograph of the untreated sample shows fiber bundles coated by gummy substances whose main component is pectin (Figure 5(a)), whereas the images of scoured samples both by chemicals (Figure 5(b)) and active water (Figure 5(c)) show well-separated fibers. 24 It can be seen that fibers treated with active water have a smoother and cleaner surface with fiber nodes clearly visible, compared with the traditional chemically scoured sample, indicating more effective gum removal from active water treatment. 25…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEM micrograph of the untreated sample shows fiber bundles coated by gummy substances whose main component is pectin (Figure 5(a)), whereas the images of scoured samples both by chemicals (Figure 5(b)) and active water (Figure 5(c)) show well-separated fibers. 24 It can be seen that fibers treated with active water have a smoother and cleaner surface with fiber nodes clearly visible, compared with the traditional chemically scoured sample, indicating more effective gum removal from active water treatment. 25…”
Section: Resultsmentioning
confidence: 99%
“…The SEM micrograph of the untreated sample shows fiber bundles coated by gummy substances whose main component is pectin (Figure 5(a)), whereas the images of scoured samples both by chemicals (Figure 5(b)) and active water (Figure 5(c)) show well-separated fibers. 24 It can be seen that fibers treated with active water have a smoother and cleaner surface with fiber nodes clearly visible, compared with the traditional chemically scoured sample, indicating more effective gum removal from active water treatment. 25 In order to study the degumming effect of active water scouring, the residual gum rate and lignin content of hemp fiber scoured with active water were tested and compared with that of raw hemp fibers and fibers scoured by traditional chemical methods.…”
Section: Scouring Of Raw Hemp Fibers Using Active Watermentioning
confidence: 98%
“…Additionally, it was observed that the microwave energy technique required less time and energy than the ultrasonic energy method when the two eco-friendly methods were compared. [80] Studying the modifications of poly (ethylene-terephthalate) fabric by ultrasound and nanoparticles of natural zeolite change the fabric surface properties. The change in chemical composition did not occur but it led to functionalization PET fabric.…”
Section: Ultrasonic Modificationmentioning
confidence: 99%
“…As a result, a fibril fiber is obtained and used as reinforcement for polymer thermoplastic composites [22]. Combined technologies of ultrasonic and chemical treatment are being introduced to change the surface structure of hemp raw materials [23]. Ultrasound is used to modify nanocellulose from hemp fibers in order to improve mechanical properties [24].…”
Section: No 4 (75) 2021mentioning
confidence: 99%